2004
DOI: 10.1099/vir.0.19652-0
|View full text |Cite
|
Sign up to set email alerts
|

IL8 release, tight junction and cytoskeleton dynamic reorganization conducive to permeability increase are induced by dengue virus infection of microvascular endothelial monolayers

Abstract: Permeability alterations of microvascular endothelia may be a factor in the plasma leakage produced by dengue virus infection. Confluent monolayers of the human dermal microvascular endothelial cell line HMEC-1 were utilized as an experimental model to study the cellular responses induced by the virus. Infected monolayers showed increased permeability for [ 3 H]mannitol, but no changes were observed for 4-70 kDa dextrans at 48 h post-infection (p.i.), a time at which viral titres reached maximal values and 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
153
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(160 citation statements)
references
References 43 publications
5
153
1
1
Order By: Relevance
“…The correlation between plasma viral load and the subsequent decline in sVEGFR2 levels lend support to this in vitro finding. Previous studies have shown increased sensitivity of endothelial cells exposed to live dengue virus to inflammatory cytokine-induced changes in permeability (42). Our observations suggest a novel mechanism by which viral factors (or host factors triggered by virus) may regulate the cleavage of surface VEGFR2, resulting in changes in soluble and surface VEGF receptors and, consequently, changes in vascular permeability.…”
Section: Discussionmentioning
confidence: 66%
“…The correlation between plasma viral load and the subsequent decline in sVEGFR2 levels lend support to this in vitro finding. Previous studies have shown increased sensitivity of endothelial cells exposed to live dengue virus to inflammatory cytokine-induced changes in permeability (42). Our observations suggest a novel mechanism by which viral factors (or host factors triggered by virus) may regulate the cleavage of surface VEGFR2, resulting in changes in soluble and surface VEGF receptors and, consequently, changes in vascular permeability.…”
Section: Discussionmentioning
confidence: 66%
“…The latter finding is particularly relevant for various pathological processes involving abnormal inflammation, angiogenesis, and/or endothelial permeability, as may occur during lung injury and tumorigenesis. As mentioned previously, IL-8 is known to play an important role in various pathological permeability events, such as those associated with lung injury (Fukumoto et al, 1998;Yamamoto et al, 1998;Laffon et al, 1999;Talavera et al, 2004). Likewise, VEGF is known to participate in lung injury-associated permeability; VEGF protein levels increase after lung injury (Karmpaliotis et al, 2002), and inhibition of VEGF signaling via soluble VEGFR2 decreased the associated permeability (Godzich et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important when considering the known role of IL-8 in increasing endothelial permeability during pathological conditions (Fukumoto et al, 1998;Yamamoto et al, 1998;Laffon et al, 1999;Talavera et al, 2004). In addition, a more comprehensive understanding of the signal transduction pathways activated by IL-8 in endothelial cells may yield insight into angiogenesis, which is important in the growth and metastasis of melanoma and nonsmall cell lung cancer (Arenberg et al, 1996;Bar-Eli, 1999;Huang et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 In another study, addition of IL-8 to monolayers of the human dermal microvascular endothelial cell line HMEC-1 caused changes in tight junction structure; the changes were inhibited by IL-8 antibodies. 23 The role of IL-8 and MCP-1 in eye disease has also been investigated. In vitro expression and production of IL-8 and MCP-1 by human retinal endothelial cells and HRPE after stimulation by pro-inflammatory cytokines have been reported.…”
Section: Il-8 and Mcp-1 In Brvo Macular Oedemamentioning
confidence: 99%